A Blockchain-Based Framework for Secure and Interoperable Healthcare Data Management: An Empirical Study - Zilong Deng; Mustafa Muwafak Alobaedy; Mohd Nurul Hafiz; Xiaocun Huang (Malikussaleh University, Aceh, Indonesia, 2025)
The digitisation of healthcare has resulted in a greater dependence on Electronic Health Records (EHRs), yet traditional centralised systems encounter ongoing difficulties with data security, interoperability, and adherence to regulations. This research presents a blockchain-oriented framework, created with Hyperledger Fabric, to tackle these constraints. Utilising a mixed-methods strategy, we assess the system's performance under normal, peak, and stress scenarios by employing one million synthetic EHR transactions. Essential metrics comprise transaction latency (2.3s), throughput (1,150 TPS), data integrity (100%), and effectiveness of access control. The results show a 30% reduction in data management errors and overall data retention. A comparative evaluation against traditional systems confirms blockchain's superior resilience and privacy safeguards. However, scalability constraints were observed during peak loads, highlighting the need for Layer-2 improvements and hybrid architectures. This research offers empirical proof validating the viability of blockchain for the secure, scalable, and regulation-compliant management of healthcare information.